Status of Climate Change and Food Security in Kathmandu District - Bhattarai, Supekshya; Nepal, Namita; Rajbhandari, Binayak P. (Nepalese Journal of Agricultural Sciences, 2025)
Climate change and its impact on agriculture and food security are serious global challenges we are facing today. This study investigates the specific impacts of climate change on agriculture and food security among farmers in Kathmandu district, Nepal. With farmers forming a significant portion of the agricultural workforce, understanding their unique challenges and adaptive strategies is crucial for developing effective interventions. Conducted over three months from April 22, 2024, to July 22, 2024, the research sampled 50 households using simple random sampling techniques. Data collection comprised both primary and secondary sources. Primary data were obtained through semi-structured interviews with respondents, field observations, and discussions with local facilitators, extension workers, and community leaders. Secondary data were gathered from published documents. The study's findings provided a detailed socio-economic profile of the respondents. Agriculture was the primary occupation for 67% of respondents, highlighting their dependence on this sector for livelihood. Land ownership patterns varied, with 34 respondents owning their land, 6 practicing sharecropping, and a few relying on leased land. Irrigation was primarily sourced from boreholes (58%), supplemented by drip irrigation, rainwater harvesting, and natural rainfall. Despite their efforts, 62% of respondents reported insufficient food production, leading to prevalent food shortages. Food insecurity was a significant issue, with 74% of respondents experiencing annual food shortages and only 24% having food security throughout the year. Many respondents resorted to purchasing food or working as laborers to meet their daily needs.